Informational constraints on predator–prey interactions. Issue 10 (19th August 2021) - Martin, Benjamin T.; Gil, Michael A.; Fahimipour, Ashkaan K.; Hein, Andrew M.
Abstract : The rates of interactions between predators and prey are fundamental to population and food web dynamics. Yet, most ecological theory of predator–prey interaction rates deals exclusively with the first phase of an interaction, an encounter, and not the second phase, a capture or escape. Here, we present a simple dynamical model of prey capture that incorporates empirically observed behavioral strategies of pursuit by predators and evasion by prey. We parameterize the model with data from aquatic systems and analyze its dynamics. Our results show that empirically observed outcomes of predator–prey interactions cannot be predicted solely from biomechanical performance traits of predators and prey. Contrary to previous work, we show that it is only through the inclusion of informational constraints – constraints on the rate at which predator and prey process and respond to incoming sensory information – that the full range of empirically observed prey capture rates are predicted by the model. Our analysis also revealed that the outcome of predator–prey interactions can largely be predicted by the product of two measurable traits: the maximum speed of the prey and the sensory‐motor delay that characterizes the time taken for the predator to respond to a change in the relative position of prey. Both of these traits exhibit power‐law scaling with body size, suggesting that simple allometric relationships may characterize the outcome of predator–prey interactions across species. More broadly, our results suggest that informational constraints can have a dominant effect on predator–prey interactions, and that these traits should be considered alongside biomechanical performance to capture the fundamental properties of predator–prey interactions in nature.